Associations between Visual Acuity and Cognitive Decline in Older Adulthood: A 9-Year Longitudinal Study. (10th December 2021) - Runk, Ashlyn; Jia, Yichen; Liu, Anran; Chang, Chung-Chou H.; Ganguli, Mary; Snitz, Beth E.
Abstract: Objective: Emerging evidence suggests low vision may be a modifiable risk factor for cognitive decline. We examined effects of baseline visual acuity (VA) on level of, and change in, cognitive test performance over 9 years. Method: A population-based sample of 1, 621 participants (average age 77 years) completed a comprehensive neuropsychological evaluation and VA testing at baseline and reassessed at nine subsequent annual visits. Linear regression modeled the association between baseline VA and concurrent cognitive test performance. Joint modeling of a longitudinal sub-model and a survival sub-model to adjust for attrition were used to examine associations between baseline VA and repeated cognitive test performance over time. Results: Better baseline VA was associated cross-sectionally with younger age, male sex, greater than high school education, and higher baseline neuropsychological test scores on both vision-dependent (B coefficient range −0.163 to −0.375, p = .006 to <.001) and vision-independent tests (−0.187 to −0.215, p = .003 to .002). In longitudinal modeling, better baseline VA was associated with slower decline in vision-dependent tests (B coefficient range −0.092 to 0.111, p = .005 to <.001) and vision-independent tests (−0.107 to 0.067, p = .007 to <.001). Conclusions: Higher VA is associated with higher concurrent cognitive abilities and slower rates of decline over 9 years in both vision-dependent and vision-independent tests of memory, language, and executive functioning. Findings are consistent with emerging literature supporting vision impairment in aging as a potentially modifiable risk factor for cognitive decline. Clinicians should encourage patient utilization of vision assessment and correction with the added aim of protecting cognition.